An assessment of the Eurocode provisions for the wind loading on low-rise buildings - Amoloye, Taofiq Omoniyi; Olayemi, Olalekan Adebayo; Oladosu, Kamoru O.; Mustapha, Kabiru (Springer, 2025)
The Eurocode provisions are cheaper alternatives to wind tunnel studies in the consideration of wind loading on a structure. Very tall buildings and large structures have enough economic justification for expensive wind tunnel studies in their design stage. Such wind tunnel studies feature simultaneous scanning and acquisition of loading data from hundreds of pressure tappings with subsequent high-speed computer data processing and analysis. This is not the case for low-rise buildings which do not find their way into the wind tunnel except in the case where they are unusual edifices. However, low-rise buildings are the most damaged in wind storms. In addition, their shapes are increasingly different from the traditional and generic forms considered in the Eurocode. Additionally, the current data acquisition techniques are more advanced than were used for the wind tunnel studies in the 80s from which the Eurocode provisions were collated. Pressures are now sampled simultaneously at all taps rather than sequentially, and tubing response is now corrected numerically rather than by optimized tubing methods. Thus, it is of interest to assess the performance of the Eurocode on present building shapes. This defined the aim of the study and its focus on low-rise buildings. In addition, the limit on the required number of pressure tapping to obtain adequate and reliable wind loading information from wind tunnel studies is investigated. The study is based on models of a simple cuboidal building, a quasi-rectangular building with inset faces in its plan, and a building plan featuring a re-entrant corner possessing curved surfaces at the internal and external junctions of its wings. It is concluded that adapting the Eurocode wind loading provisions to irregular building plans characteristic of modern times may give unsafe solutions. The variations of pressure with wind direction on the internal walls of the wings and the curved surface at the internal junction of the re-entrant corner follow coherent wave forms that are mutually similar. These can be further investigated for codification purposes.
Keywords: 49 Mathematical sciences; 51 Physical sciences; Cuboidal building; Irregular building plan; Pressure tapping; Tributary area